THE RELATIONSHIP BETWEEN WAIST CIRCUMFERENCE AND SYSTOLIC BLOOD PRESSURE - Miranti Dewi Pramaningtyas; Kaka Citta Prasiddha; Reza Ishak Estiko (Fakultas Kedokteran, Universitas Palangka Raya, 2021)
This cross-sectional study reported a link between waist circumference as an anthropometric index for central obesity and systolic blood pressure. The study used a cross-sectional method by linking systolic blood pressure data and waist circumference. A total of 45 male and female participants met the inclusion criteria in the study. The average waist circumference (cm) is 79.90 ± 10.41, and the average systolic blood pressure (mmHg) is 107.28 ± 11.01. Of all participants, 84.4% had normal systolic blood pressure, 13.3% prehypertension, 2.2% stage 1 hypertension. For waist circumference, 21 out of 27 men in the central obesity category (77.8%) had a normal waist circumference (22.2%). On the other hand, 6 out of 18 women are centrally obese (33.3%), and 12 women have a normal waist circumference (66.7%). Spearman's correlation results show p=0.344. Research shows that there is a relationship between waist circumference and systolic blood pressure with a weak correlation.